As atividades circenses na educação física escolar - Nunes, Elaine Catarina Geraldes (2024)
Circus activities have been manifested throughout history, transforming and adapting to different contexts and social realities. In the last two decades we have noticed exponential growth in the offer of this body practice as a curricular component, especially in school Physical Education classes and other educational spaces. This phenomenon is noticeable both in the international scene (Coasne, 1992; Invernó, 2003; Fodella, 2000; ) and in the national one (Bortoleto, Machado, 2003), with a tendency to expand further. The research analyzed the conceptions of students about the insertion of circus activities in the school physical education classes, providing these students with the experimentation of different forms of body and social language, focusing on the elaboration of activities that could be chosen and practiced by all students, promoting the development of the potential of these students in their different aspects in the training process beyond the physical and motor, that is, seeking integral human formation. The survey took place at Escola Estadual Ana Maria das Graças Noronha, in the municipality of Cáceres-MT, with students from the 3rd year of high school, a class composed of 25 (twenty five) students. We developed this study based on a qualitative approach with assumptions of the theoretical framework of action research using instruments for data collection: initial (diagnosis) and final questionnaires (after the development of the didactic unit), field notebook, systematic observation script, photographs and videos. We conclude that circus activities are rich and have great potential as cultural expression and as school content, with its modalities profitably opportunized the construction of new knowledge, recognition of the possibilities of movements beyond the activities traditionally developed in Education classes.